2014
DOI: 10.1007/s00404-014-3448-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sperm cell source on the results of intracytoplasmic sperm injection

Abstract: Neither the source of spermatozoa nor the etiology of severe male infertility has relevant impact on the results of ICSI cycles as long as fresh motile, morphologically normal spermatozoa are used. Therefore, in case of cryptozoospermia, we recommend to preferentially use ejaculated spermatozoa to prevent those men from an unnecessary testicular biopsy avoiding risks and costs implied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Lu et al found a slight advantage of ejaculated sperm in terms of fertilization rates and embryo quality within one center’s large experience [4]. Similarly, Gnoth and colleagues analyzed 337 IVF-ICSI cycles and found no difference in clinical outcomes between ejaculated and testicular sperm for men with cryptozoospermia [6]. Both studies were limited by a retrospective design with significant potential for selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al found a slight advantage of ejaculated sperm in terms of fertilization rates and embryo quality within one center’s large experience [4]. Similarly, Gnoth and colleagues analyzed 337 IVF-ICSI cycles and found no difference in clinical outcomes between ejaculated and testicular sperm for men with cryptozoospermia [6]. Both studies were limited by a retrospective design with significant potential for selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, this tenet is increasingly being challenged as IVF-ICSI outcomes correlate poorly with traditional sperm quality parameters [4, 5]. Studies involving large cohorts have now shown near equivalence with samples retrieved from the epididymis or testis [68], and even with sperm characterized by poor motility and morphology [5]. In the extreme scenario of substantial necrospermia, testicular sperm may even outperform viable ejaculated samples [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although intracytoplasmic sperm injection (ICSI) is a remarkably effective technique in allowing fatherhood in men previously considered sterile, sperm retrieval from the epididymis or testis should be the last option to be given to men. Gnoth et al showed that the source of spermatozoa has not relevant impact on the results of ICSI cycles as long as fresh motile, morphologically normal spermatozoa are used, proposing, in case of cryptozoospermia, to preferentially use ejaculated spermatozoa to prevent those men from an unnecessary testicular biopsy avoiding risks and costs implied ( 12 ). In addition, the use of a single sperm found in ejaculate in ICSI resulting in successful pregnancy was demonstrated by Desai et al ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Owed to its complex nature, we have advocated that semen analysis should be ideally carried out in Andrology Laboratories equipped with experienced technicians and validated systems, and enrolled in internal and external quality control programs ( 3 , 8 , 9 , 12 ). In this current issue of Int Braz J Urol, Monteiro and colleagues shed light on this very same issue ( 1 ).…”
mentioning
confidence: 99%
“…However, testicular sperm retrieval does carry risk for the male patient—it is an invasive surgical procedure with potential complications including but not limited to bleeding, infection, and irreversible testicular tissue damage (Gnoth et al ., ). We therefore need to be cautious when recommending this procedure to patients to ensure the potential benefits outweigh the risks.…”
Section: Introductionmentioning
confidence: 97%